Penerapan Protokol Kesehatan Covid-19 pada Idul Fitri 1441 H di Perum Griya Nato Ujung Gurap - Antoni, Adi; Hidayah, Arinil (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2020)
Covid-19 is an infectious disease caused by the corona virus. The virus is transmitted through droplets that are produced when an infected person coughs, sneezes, or exhales. The purpose of this community service is to provide education to residents of Griya Nato 1, regarding the health protocol for the prevention of Covid-19 on Eid al-Fitr 1441 H. The method used in this community service activity was online based using the WhatsApp application. This activity was carried out for 1 hour on Wednesday May 20 2020 (D-4 Eid 1441 H). The target of this activity is the residents of the Griya Nato 1 housing complex, Ujung Gurap village. The method given is in the form of educational materials and problems related to the implementation of Eid Al-Fitr prayers and activities carried out during Eid. The results obtained after this service activity were an increase the knowledge of housing residents about the management and implementation of Eid al-Fitr activities ranging from Eid prayers at home to online gathering activities. In addition, health protocols related to hand washing, use of hand sanitizer and wearing of masks were also provided. The results of this service can be applied by residents of housing in the prevention of Covid-19 in the Griya Nato 1 residents.